2012
DOI: 10.1007/s00464-012-2582-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of robot-assisted laparoscopy in nerve-sparing radical hysterectomy: urinary morbidity in early cervical cancer

Abstract: Nerve-sparing radical hysterectomy by robot-assisted laparoscopy is feasible in early cervical cancer (<2 cm). A total of 93.3 % of the patients were discharged 2 days after surgery with spontaneous voiding. The next step would be a prospective study with objective urodynamic investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…11,12,22,29 On the other hand, it is well demonstrated that postoperative adjuvant radiotherapy is a significant cause of morbidity. [31][32][33][34] Interestingly, our literature search showed that up to 54 % of patients with cervical cancer underwent adjuvant radiation therapy after NSRH (Table S1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12,22,29 On the other hand, it is well demonstrated that postoperative adjuvant radiotherapy is a significant cause of morbidity. [31][32][33][34] Interestingly, our literature search showed that up to 54 % of patients with cervical cancer underwent adjuvant radiation therapy after NSRH (Table S1).…”
Section: Discussionmentioning
confidence: 98%
“…16 Thus, we were able to find seven retrospective studies focused mainly on oncologic outcomes of NSRH. 11,13,14,17,23,24,28 Outcomes Our literature search found heterogeneous oncologic outcomes ranging from no overall recurrences 15,17,19,20,22,25,27,29 to an overall recurrence rate of 19.6 % 28 after NSRH.…”
Section: Study and Patient Characteristicsmentioning
confidence: 98%
“…34 Various smaller studies (n = 18, 13, 23, 30) showed low recurrence rates with a median follow-up time of 33.3, 12, 24.5, and 11.5 months. 13,15,25,30 In our series, we also included patients with locally advanced cervical cancer (stage IB2, IIA2, and IIB) who were treated preoperatively with 9 weeks of NACT. The surgicopathological outcomes were comparable for the early stage and the locally advanced cases.…”
Section: Discussionmentioning
confidence: 99%
“…8,19 Several investigations suggested that the use of minimally invasive rather than open surgery and NS rather than non-NS approaches improve postsurgical patients' outcomes. 4,9 In particular, laparoscopy minimizes the effects of abdominal trauma, and the NS technique reduces the effects of iatrogenic denervation of the vagina and lower urinary and rectal tracts. However, only limited data about the use of these combined techniques (ie, NS-LRH) are still available.…”
Section: Discussionmentioning
confidence: 99%